Design and implementation of access monitoring and control based on SCADA system - Hasan Mohammed Jawad Jasim Al-Jazaeri; Amer Abdulmahdi Jabbar Chlaihawi (Institute of Advanced Engineering and Science, 2022)
The supervisory control and data acquisition (SCADA) system is considered a pioneer system in the field of remote education. Three laboratories are designed for the alternating current (AC) Machine Lab, while the programmable logic controller (PLC) is used to connect the system to the Internet by designing an interface to the system through the DIAView program, where each student has his account and a specific time to implement the experiment and write the result in a report window. In this system, teacher and students can assess the system through a specific window. The teacher can access, control and monitor the performance of the students. The teacher can evaluate each student. Student can access and control the laboratories. The methods to turn on the single-phase induction motor include capacitors, auto transformer and variable frequency drive (VFD). VFD is considered an advanced system at present, to which an intelligent system has been added. Moreover, an overload protection system has been introduced, where it would shut down the Lab and show an error message. The system can work as a local area and public area when connected to the university of KUFA system Moodle server.